ANALISIS KESULITAN PESERTA DIDIK DALAM MENENTUKAN IDE POKOK PADA TEKS CERITA NARASI KELAS lV SD NEGERI BABADSARI - Bayu Fatah Alam; Titi Anjarini; Muflikhul Khaq (STKIP Subang, 2024)
This study aims to 1) The difficulties experienced by students are not yet mastering the main idea, difficulty in determining the main sentence and difficulty when finding sentences that are too long in a paragraph. 2) Students have difficulty in determining the main idea and explanatory ideas/supporting ideas. to find out the difficulties of students in determining the Main Idea in Narrative Story Texts of Grade IV Elementary School Babadsari. This type of research is descriptive qualitative. The subjects of the study were 18 grade IV students of Elementary School Babadsari. The object of the study was the results of student tests on the main idea of ​​the paragraph in the reading text